GAYA BAHASA HIPERBOLA DALAM NOVEL PULANG KARYA TERE LIYE - Etami, Gemmi; Hamsa, Akmal; Baharman, Baharman (Fakultas Bahasa dan Sastra Indoensia, 2025)
This research aims to: describe the characteristics of hyperbolic language style and describe the function of using hyperbolic language style in the novel